Demographic and socio‐economic differences between men seeking infertility evaluation and those seeking surgical sterilization: from the National Survey of Family Growth. (25th March 2015) - Hotaling, James M.; Patel, Darshan P.; Brant, William O.; Myers, Jeremy B.; Cullen, Mark R.; Eisenberg, Michael L.
<x xml:space="preserve">Abstract</x> Objective To identify differences in demographic and socio‐economic factors between men seeking infertility evaluation and those undergoing vasectomy, to address disparities in access to these services. Patients and Methods Data from Cycle 6 and Cycle 7 (2002 and 2006–2008) of the National Survey of Family Growth (NSFG) were reviewed. The NSFG is a multistage probability survey designed to capture a nationally representative sample of households with men and women aged 15–45 years in the USA. The variables analysed included age, body mass index, self‐reported health, alcohol use, race, religious affiliation, marital status, number of offspring, educational attainment, income level, insurance status and metropolitan home designation. Our primary outcome was the correlation of these demographic and socio‐economic factors with evaluation for male infertility or vasectomy. Results Of the 11 067 men identified through the NSFG, 466 men (4.2%) sought infertility evaluation, representing 2 187 455 men nationally, and 326 (2.9%) underwent a vasectomy, representing 1 510 386 men nationally. Those seeking infertility evaluation were more likely to be younger and have fewer children (P = 0.001, 0.001) and less likely to be currently married (78 vs 74%; P = 0.010) or ever married (89 vs 97%; P = 0.002). Men undergoing a vasectomy were more likely to be white (86 vs 70%; P = 0.001). Men seeking infertility evaluation were more likely to have a college or graduate degree compared with men undergoing a vasectomy (68 vs 64%; P = 0.015). There was no difference between the two groups for all other variables. Conclusion While differences in demographic characteristics such as age, offspring number and marital status were identified, measures of health, socio‐economic status, religion and insurance were similar between men undergoing vasectomy and those seeking infertility services. These factors help characterize the utilization of male reproductive health services in the USA and may help address disparities in access to these services and improve public health strategies.